Design of a web-based online reservation system for the pediatric polyclinic at Bhina Bhakti Husada Hospital - Indra Prasetya; Syakur; Fajar Sodiq (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
Bhina Bhakti Husada Hospital faces operational constraints in the Pediatric Clinic service due to a manual reservation system relying on direct registration and WhatsApp, resulting in long queues and data recording errors. This research aims to design and implement a web-based online reservation system integrated with doctor schedules and a real-time queuing system using MERN Stack technology (MongoDB, Express.js, React.js, and Node.js). The research method employs a qualitative descriptive approach for requirements analysis and the Prototyping method for system development, with functionality testing using Black box Testing. Test results demonstrate that all designed testing scenarios were successfully executed according to system specifications. The developed system significantly improves service efficiency by reducing reservation processing time from 10-15 minutes to 2-3 minutes and provides data transparency through a real-time administrative dashboard. This research contributes to enhancing the quality of Pediatric Clinic healthcare services through automation of reservation and queue processes, with recommendations for further development including online payment integration, automatic notifications, and mobile applications.